Concepts associated with episthemic emotions in recent research - Riveros-Garzón, Jeimy Patricia; Ocampo-Flórez, Esteban (Rastros Rostros, 2026)
Starting from epistemic emotions, the constructs that have been associated with them are identified, highlighting the processes that are affected in said interaction. The findings indicate that epistemic emotions have been related, especially to three constructs: epistemic beliefs, learning and didactics, and metacognitive adaptation. From these interactions, effects were found on learning strategies, academic performance, decision making, motivation, overcoming challenges, metacognitive skills, and emotional regulation, allowing the identification of emotions that facilitate or hinder learning. It is concluded that knowledge of the dynamics of epistemic emotions in relation to other processes contributes to enhancing learning, improving didactics, and favoring the selection of strategies for the acquisition of knowledge by students.